Penghitungan Biaya Satuan pada Instalasi Rawat Jalan di Rumah Sakit X Jambi menggunakan Metode Step Down - Wulan, Susilo; Direja, Ade Herman Surya; Reflisiani, Dian (Jurnal Ekonomi Kesehatan Indonesia, 2019)
Hospital has a responsibility to provide quality and affordable health care to the community. Therefore, determining tariffs by calcu lating the actual cost is very important, especially for internal stakeholders in undergoing cost analysis, performance evaluation and decision making, including tariff negotiation with external stakeholders. This research objective is to calculate unit costs and compar atively analyzing costs between units in an outpatient installation using the step-down method. This research used a partial economic evaluation which only portrays the description of cost object without comparing the output from the analyzed unit. The stages of data analysis include identifying the resource of cost center by firstly determining the final cost, intermediate cost and indirect cost, the second stage is identifying and calculating investment cost, operational cost, and maintenance costs, the third stage is determining the allocation basis, and the fourth stage is calculating the total cost. The highest unit cost occurs in dental poly at Rp.621.100,99/visit, while the lowest unit cost is in internal medicine which is Rp.241.307,51/visit. It is hoped that the results of this study can be taken into consideration in the changes made by service rates and making evaluation materials on outpatient care so that they are more efficient in their management.